Asymmetry of Achilles tendon mechanical and morphological properties between both legs. Issue 1 (5th May 2014) - Bohm, S.; Mersmann, F.; Marzilger, R.; Schroll, A.; Arampatzis, A.
<x xml:space="preserve">Abstract</x> Although symmetry of Achilles tendon (AT) properties between legs is commonly assumed in research and clinical settings, different loading profiles of both legs in daily life (i.e., foot dominance) may affect the tendon properties in a side‐depended manner. Therefore, AT properties were examined with regard to symmetry between legs. Thirty‐six male healthy adults (28 ± 4 years), who were physically active but not involved in sports featuring dissimilar leg load participated. Mechanical and morphological AT properties of the non‐dominant and dominant leg were measured by means of ultrasound, magnetic resonance imaging and dynamometry. The AT of the dominant leg featured a significant higher Young's modulus and length (P < 0.05) but a tendency toward lower maximum strain (P = 0.068) compared with the non‐dominant leg. The tendon cross‐sectional area and stiffness were not significantly different between sides. The absolute asymmetry index of the investigated parameters ranged from 3% to 31% indicating poor AT side symmetry. These findings provide evidence of distinct differences of AT properties between both legs in a population without any sport‐specific side‐depended leg loading. The observed asymmetry may be a result of different loading profiles of both legs during daily activities (i.e., foot dominance) and challenges the general assumption of symmetrical AT properties between legs.